Socialization of the Implementation of the Village Financial System Application for Village Government Officials - Andi Hafidah; Rizki Wahyuni; Imriani Idrus (Jurnal Pengabdian Pancasila (JPP), 2022)
Siskeudes is a village finance application developed in 2015 by the Financial and Development Supervisory Agency (BPKP). The socialization of the implementation of the SISKEUDES application aims to help understand and increase the knowledge of village officials regarding the application of the village financial system so that they can improve the performance of the Lempangan village government apparatus, Gowa Regency. The method used is the socialization/counseling method. The SISKEUDES application implementation model consists of 4 (four) dimensions: planning, budgeting, administration, reporting and accountability. The results obtained are that the socialization of the implementation of the SISKEUDES application can improve the performance of village government officials.